The Influence of Teachers' Positive Politeness Strategies on Students' Self-Efficacy in Indonesian Language Learning in Senior High School - Miftahul Afifur Rohman; Agusniar Dian Savitri; Yuniseffendri (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to analyze the influence of teachers’ positive politeness strategies on students’ self-efficacy in Indonesian language learning. The research examines how teachers’ communication strategies can strengthen students’ confidence in their ability to understand and complete learning tasks. Using a quantitative approach, the study involved Grade XI students from SMA Muhammadiyah 4 Surabaya as participants, selected through purposive sampling. Data were collected using questionnaires and analyzed through several stages: (a) validity and reliability testing, (b) classical assumption testing (normality, heteroscedasticity, and linearity tests), (c) simple linear regression analysis, and (d) hypothesis testing (t-test and coefficient of determination). The results indicate that teachers’ positive politeness strategies significantly influence students’ self-efficacy in Indonesian language learning. This is evidenced by an R Square value of 0.552, demonstrating that the politeness strategy variable explains 55.2% of the variation in students’ self-efficacy levels. This study contributes to the field of educational communication by empirically demonstrating that teachers’ use of positive politeness strategies fosters greater student confidence and engagement in language learning. The findings highlight the importance of teacher–student interaction styles as a key factor in enhancing self-efficacy and overall learning effectivenes.